Transanal Repair of Rectourethral and Rectovaginal Fistulas - Razi, Ali Razi; Yahyazadeh, Seyed Reza Yahyazadeh; Gilani, Mohammad Ali Sedighi Gilani; Kazemeyni, Seyed Mohammad Kazemeyni (Urology Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: We evaluated the efficacy and safety of repair of the rectourethral and rectovaginal fistulas with transanal approach using the Latzko technique. Materials and Methods: We repaired 8 fistulas with transanal approach. Fistulas were rectourethral in 5 patients, and in the only woman of the series, they were rectovaginal and vesicovaginal. In 3 patients, The fistulas had been diagnosed following prostatectomy, urethral stricture repair, and colonic resection and radiotherapy due to rectosigmoid cancer in 3, 2, and 1 patients, respectively. Complying with Latzko technique, the fistula orifice was exposed and a fusiform incision was made with the orifice in its center. The mucosa lying between the incision and the orifice was excised in the direction of the incision to the orifice, leaving the fistula edges to meet. Then, the edges were closed, followed by closure of the muscular layers above it. Finally, the edges of the rectal mucosa were closed Results: Two patients had 2 fistulas and 4 had 1 fistula who were all managed by transanal approach. During a median follow-up period of 44 months, no serious complication was noted, except for recurrence of deep vein thrombosis in 1 patient with a positive history for this complication. Hospitalization period was 1 to 7 days. Conclusion: It seems that transanal repair is a simple and effective technique with minimal complication rate in the treatment of rectourethral fistulas. Regardless of the etiology, this method can be used as the preferred therapeutic technique. Further studies are necessary to confirm our findings.